A simple method for isocapnic hyperventilation evaluated in a lung model. Issue 5 (21st December 2015) - Hallén, K.; Stenqvist, O.; Ricksten, S.‐E.; Lindgren, S.
Abstract : Background: Isocapnic hyperventilation (IHV) has the potential to increase the elimination rate of anaesthetic gases and has been shown to shorten time to wake‐up and post‐operative recovery time after inhalation anaesthesia. In this bench test, we describe a technique to achieve isocapnia during hyperventilation (HV) by adding carbon dioxide (CO2 ) directly to the breathing circuit of a standard anaesthesia apparatus with standard monitoring equipment. Methods: Into a mechanical lung model, carbon dioxide was added to simulate a CO2 production ( V co 2 ) of 175, 200 and 225 ml/min. Dead space ( V D ) volume could be set at 44, 92 and 134 ml. From baseline ventilation (BLV), HV was achieved by doubling the minute ventilation and fresh gas flow for each level of V co 2, and dead space. During HV, CO2 was delivered ( D co 2 ) by a precision flow meter via a mixing box to the inspiratory limb of the anaesthesia circuit to achieve isocapnia. Results: During HV, the alveolar ventilation increased by 113 ± 6%. Tidal volume increased by 20 ± 0.1% during IHV irrespective of V D and V co 2 level. D co 2 varied between 147 ± 8 and 325 ± 13 ml/min. Low V co 2 and large V D demanded a greater D co 2 administration to achieve isocapnia. The FICO2 level during IHV varied between 2.3% and 3.3%. Conclusion: It is possible to maintain isocapnia during HV by delivering carbon dioxide through a standard anaesthesia circuit equipped with modern monitoring capacities. From alveolar ventilation, CO2 production and dead space, the amount of carbon dioxide that is needed to achieve IHV can be estimated.